Wireless body area networks: applications and congestion control technologies - Al-Hiti, Ahmed Shakir; Sahbudin, Ratna K. Z.; Harun, S. W.; Obaid, Ammar Naser; Hamdi, Mustafa Maad; Al-Shareeda, Mahmood A. (IEEE, 2023)
Wireless body area networks (WBANs) have been used widely as sensor nodes are implanted into the body, on the body, or around the body. Many methods have been proposed concerning different issues existing in this network. Congestion is one of the vital and earnest problems in the transport layer. So, researchers are looking for a solution to avoid congestion in the network to properly transfer data between the nodes. In this work, we provide a review of WBANs applications and also congestion methods that have been proposed in WBANs. The congestion methods can be optimized through the performance parameters like delay, throughput, packet loss, data rate, and queue length.